PENGARUH AGAMA TERHADAP KEKUASAAN RAJA-RAJA MATARAM - AR, Syukrianto (Jurnal Bestari, 1993)
The history of java cannot be separated from the history of Javanese kingdoms. One of them is Mataram. This kingdom has a capital in Yogyakarta and can be considered as ?the last kingdom? exists until recent time. One of the most interesting characteristics of Mataram is the correlation and interaction between Islamic teachings and the Kings.